Apparent Contradictions in the Verses of Legal Rulings: An Analytical Study - Hafiz Muhammad Asghar Shakir; Dr. Mahmood Ahmad (Corresponding Author) (Journal of Religion and Society, 2025)
This research paper critically examines the the perceived contradictions in the Qur’anic legal verses (Āyāt al-Aḥkām), a subject often targeted by critics to undermine the coherence of Islamic law. The study explores several key areas where contradictions are alleged, such as the rulings on fasting, punishment for adultery, the waiting period (‘iddah) for widows, and the principle of non-coercion in religion. Through a detailed analysis grounded in principles of abrogation (naskh), linguistic clarity, and contextual interpretation, the paper demonstrates that these objections are based on superficial readings or ignorance of Islamic legal methodology. The study confirms that the Qur’anic legal framework is both internally coherent and systematically structured, and that any perceived conflict dissolves when viewed through the lens of traditional exegesis and jurisprudence. Keywords: Qur’anic Law, Apparent Contradictions, Abrogation (Naskh), Āyāt al-Aḥkām, Islamic Jurisprudence, Legal Hermeneutics, Qur’anic Consistency, Fiqh, Tafsir.